PREDICTORS OF CLINICAL OUTCOMES IN INDIAN PATIENTS WITH ACUTE ENCEPHALOPATHY: A PROSPECTIVE OBSERVATIONAL STUDY FROM A TERTIARY CARE CENTER IN INDIA - S, MURALI; S, SUHANA; N, RAVAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Objective of the study was to evaluate the predictors of poor disease outcome at discharge and at 1 month in patients with acute encephalopathy. Methods: This prospective, observational, single center study included adult patients meeting the diagnostic criteria for acute confusion state and admitted in the intensive care unit of a tertiary care hospital. A modified Rankin Scale (mRS) score of <3 was considered as “good outcome,” while mRS ≥3 was considered as an indicator of “poor outcome.” Results: Among the total population of 219, 52.5% (n=115) were male, the mean age was 41.58 (±18.10) years and mean disease duration was 14.30 (±10.05) days (range: 1–30 days). Lethargy was the most common history at presentation (84.93%), while sleep abnormalities were least common (4.57%), and tuberculous meningitis was the most common etiology (21%). Diminution of vision, diplopia, dysarthria, cranial nerve symptoms, abdominal pain, difficulty in breathing, seizures, high-risk behavior, loss of appetite and the diagnosis of posterior reversible encephalopathy, retroviral disease, stroke and tuberculous meningitis were significant predictors of “poor outcome” at discharge (p<0.05). A diagnosis of tuberculous meningitis, history of headache, diminution of vision, diplopia, dysarthria, seizures, sensory deficits and loss of appetite and neuroimaging findings of atrophy, intracranial bleeding, demyelination, and space-occupying lesion were found to be significant predictors of “poor outcome” at 1 month post-discharge in this population (p<0.05). Conclusion: In patients with acute encephalopathy, tuberculous etiology, the presence of focal brainstem deficits and specific neuroimaging findings indicate poor outcomes at discharge as well as at 1 month follow-up.